Mid-infrared fibre evanescent wave spectroscopy of serum allows fingerprinting of the hepatic metabolic status in mice. Issue 22 (26th September 2016) - Le Corvec, Maëna; Allain, Coralie; Lardjane, Salim; Cavey, Thibault; Turlin, Bruno; Fautrel, Alain; Begriche, Karima; Monbet, Valérie; Fromenty, Bernard; Leroyer, Patricia; Guggenbuhl, Pascal; Ropert, Martine; et al.
Abstract : Infrared spectroscopy from mice unveils a transition in the time course of steatosis. Abstract : Non-alcoholic fatty liver disease is associated with obesity, diabetes, and metabolic syndrome. The detection of systemic metabolic changes associated with alterations in the liver status during non-alcoholic fatty liver disease could improve patient follow-up. The aim of the present study was to evaluate the potential of mid-infrared fibre evanescent wave spectroscopy as a minimum-invasive method for evaluating the liver status during non-alcoholic fatty liver disease. Seventy-five mice were subjected to a control, high-fat or high-fat–high carbohydrate diets. We analysed the serum biochemical parameters and mRNA levels of hepatic genes by quantitative RT-PCR. Steatosis was quantified by image analysis. The mid-infrared spectra were acquired from serum, and then analysed to develop a predictive model of the steatosis level. Animals subjected to enriched diets were obese. Hepatic steatosis was found in all animals. The relationship between the spectroscopy-predicted and observed levels of steatosis, expressed as percentages of the liver biopsy area, was not linear. A transition around 10% steatosis was observed, leading us to consider two distinct predictive models (<10% and >10%) based on two different sets of discriminative spectral variables. The model performance was evaluated using random cross-validation (10%). The hypothesis that additional metabolic changes occur beyond this transition was supported by the fact that it was associated with increased serum ALT levels, and Col1α1 chain mRNA levels. Our data suggest that mid-infrared spectroscopy combined with statistical analysis allows identifying serum mid-infrared signatures that reflect the liver status during non-alcoholic fatty liver disease.